Scholarly publishing and peer-review in times of crisis: an overview - Henriques, Susana Oliveira (2022)
© 2022 The Author(s), licensee HBKU Press. This is an Open Access article distributed under the terms of the Creative Commons Attribution license CC BY 4.0 (https:// creativecommons.org/licenses/ by/4.0), which permits unrestricted use, distribution and reproduction in any medium, provided the original work is properly cited.